2009
DOI: 10.1016/j.bcp.2009.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 supplementation lowers hepatic oxidative stress and inflammation associated with diet-induced obesity in mice

Abstract: Please cite this article as: Sohet FM, Neyrinck AM, Pachikian BD, de Backer FC, Bindels LB, Niklowitz P, Menke T, Cani PD, Delzenne NM, Coenzyme Q10 supplementation lowers hepatic oxidative stress and inflammation associated with diet-induced obesity in mice, Biochemical Pharmacology (2008Pharmacology ( ), doi:10.1016Pharmacology ( /j.bcp.2009 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
78
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(97 citation statements)
references
References 53 publications
12
78
0
7
Order By: Relevance
“…In another study, CoQ10 supplementation significantly reduced the IL-6 protein and TGF-b1 and Lep mRNA levels [6]. In addition, our study was in agreement with findings in cardiac tissue [23], and CoQ10 is known to have anti-inflammatory properties in mouse liver [24] and human plasma [25]. Also, gene expression of TNF-a were significantly decreased following CoQ10 intake in an experimental model of multiple sclerosis for three weeks [26].…”
Section: Discussionsupporting
confidence: 76%
“…In another study, CoQ10 supplementation significantly reduced the IL-6 protein and TGF-b1 and Lep mRNA levels [6]. In addition, our study was in agreement with findings in cardiac tissue [23], and CoQ10 is known to have anti-inflammatory properties in mouse liver [24] and human plasma [25]. Also, gene expression of TNF-a were significantly decreased following CoQ10 intake in an experimental model of multiple sclerosis for three weeks [26].…”
Section: Discussionsupporting
confidence: 76%
“…CoQ10 has been reported to have beneficial effects on the heart, lungs, liver, and skin. 1,2 It has been shown that by lowering matrix metalloproteinase levels in fibroblasts, CoQ10 reduces wrinkles. 3 CoQ10 also exerts anti-inflammatory effects on dermal fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a randomized human clinical trial documented a significant improvement in NASH in nondiabetic subjects after long-term vitamin E administration compared to pioglitazone (186). Additionally, the observation of reduced systemic coenzyme Q10 levels in patients with NAFLD (223) has lead to limited investigation of the effects of dietary supplementation of coenzyme Q. Coenzyme Q10 supplementation has been observed to lower oxidative stress and markers of inflammation in a mouse, without modulating lipid peroxidation or improving systemic insulin resistance (195). Additionally, coenzyme Q9 monomethyl ether administration increased VLDL assembly in rats with high-fat-diet-induced steatosis (22,182), with no observed improvement in NAFLD or systemic insulin resistance (182).…”
Section: Pharmaceutical and Antioxidant Therapiesmentioning
confidence: 99%